Effectivity of Earthworm (Lumbricus rubellus) Extract as Antidiarrhea Caused by Enteropathogenic Escherichia Coli - Irawan, Angeline Aprilia; Putri, Gita Almira; Dhumaranang, Hyangayu Dedari; Indrayani, Agung Wiwiek (Jurnal Epidemiologi Kesehatan Komunitas, 2024)
Background: Diarrhea still becomes a health problem in Indonesia with a high mortality rate among children under five years old. Antibiotics are used in the management of diarrhea caused by Enteropathogenic Escherichia coli, but it can change the intestinal microbiota in children and can cause resistance. Therefore, raw material is needed as an antibacterial.Methods: The sources of the narrative review come from Google Scholar, PubMed, and ResearchGate with keywords such as earthworm, Lumbricus rubellus, earthworm extract, antidiarrhea, and Escherichia coliResult: Earthworms (Lumbricus rubellus) have some active compounds that are useful for fibrinolytic, thrombolytic, antithrombotic, anti-inflammatory, antioxidant, and broad-spectrum antimicrobial properties. The antimicrobial activity of earthworms is due to the presence of Lumbricin-1 content where its activity against Escherichia coli has been proven by various studies.Conclusion : Earthworm (Lumbricus rubellus) extract can inhibit the growth of Escherichia coli bacteria so it has the potential to become an antidiarrheaKeywords: antidiarrheal; earthworm; Lumbricus rubellus; Lumbricin-1; Enteropathogenic Escherichia coli